The murderer's daughter: a novel (Ballantine Books, 2015)
"Grace Blades is a master psychologist, respected by her peers and adored by her patients. She is hard working and highly competent, a model of self-control. But in private, Grace indulges a secret thrill-seeking darkness, pursuing danger as an escape from the regimented life she's established. Closing her eyes as she flies down the Los Angeles freeway or targeting a stranger in a hotel bar for an anonymous moment of passion, Grace craves the rush. Order by day, danger by night - the double life helps her cope with memories of a traumatic childhood, in which Grace saw her mother stab her abusive father before turning the knife on herself. But her two worlds collide when a new patient turns out to be her random conquest from the night before. He pleads for her to take him on anyway, claiming a unique connection with the foster father who raised her. She refuses. The next day, his body is found by police with only her business card to identify him. Suddenly, Grace is plunged into a web of danger and deceit that will draw her back into the dark past she fought so hard to leave behind"--

Against all odds: a novel (Delacorte Press, Recorded Books, Findaway World, LLC, 2017)
"Against All Odds is the wise, moving new novel from Danielle Steel, whose many #1 New York Times bestselling tales have made her one of America's favorite authors"-- "The story of a long-widowed proprietor of a top flight haute couture resale shop and her four adult children, who, in their search to find the right partners for themselves, encounter and struggle with some very difficult and modern problems facing young people today"--

New: understanding our need for novelty and change (Penguin Press, 2011)
Offers insight into the psychological drive to pursue new things, sharing advice for aficionados of new experiences on how to embrace today's dynamic and creative culture while living sensibly and satisfyingly.

What do you do with a chance? (Compendium, Compendium, Inc, 2017)
This is a story for anyone who has ever wanted something, but was afraid of risking too much to get it. It's a story to inspire you to embrace the chances that come into your life. You never know when a chance, once taken, might be the one to change everything.

The king's justice (Maggie Hope Mysteries, 9,, 2020)
"London. December, 1942. As the Russian army repels German forces from Stalingrad, Maggie Hope, secret agent and spy, takes a break from the Special Operations Executive division to defuse bombs in London. But Maggie herself is like an explosion waiting to happen. Shaken by a recent case, she finds herself living more dangerously--taking more risks than usual, smoking again, drinking gin and riding a motorcycle--and the last thing she wants is to get entangled in another crime. But when she's called upon to look into a stolen Stradivarius, one of the finest violins ever made, Maggie finds the case too alluring to resist. Meanwhile, there's a serial killer on the loose in London and Maggie's skills are in demand. Little does she know that in the process of investigating this dangerous predator, she will come face to face with a new sort of evil...and discover a link between the precious violin and the murders no one could ever have expected"--

Adult ADHD: how to succeed as a hunter in a farmer's world (Park Street Press, 2016)
Description Not Provided